Strike of Truck Drivers: Analysis of the Conduct of Fuel Stations in Sousa-PB under the Antitrust Law (Research, Society and Development, 2019)
The present research brings as main an analysis on the search of the truck drivers, that can trigger the national decision making and, therefore, widely reported between May and June 2018. explanation about the social enemies at local level in the municipality of Sousa-PB. So this is a case study. Law no. 12,529 / 2011, an Antitrust Law, based on the rules issued by the city's Consumer Protection and Protection Program. The indicators that are pointed to several factors that cause the truck drivers' demand, besides being informative about the political and social, besides the finding of conduct contrary to the Antitrust Law by the fuel stations.